Effects of an Angiotensin-converting Enzyme Inhibitor-based Regimen on Pneumonia Risk - Ohkubo, Takayoshi; Chapman, Neil; Neal, Bruce; Woodward, Mark; Omae, Teruo; Chalmers, John (American journal of respiratory and critical care medicine, 2004)
Observational studies conducted among Asian populations suggest that the risk of pneumonia is substantially reduced among users of angiotensin-converting enzyme (ACE) inhibitors but not other blood pressure-lowering agents. We conducted analyses of the effects of ACE inhibitor therapy on pneumonia in 6,105 patients with a history of stroke or transient ischemic attack enrolled in a randomized trial conducted in Australasia, Europe, and Asia. Patients were randomly assigned perindopril-based active treatment or placebo. The effects of ACE inhibitors on pneumonia (fatal or nonfatal) were determined from Cox models fitted according to the principle of intention to treat. During a median follow-up of 3.9 years, 261 patients developed pneumonia. Overall, active treatment was associated with a nonsignificant 19% lower risk of pneumonia (95% confidence interval, -3 to 37; p = 0.09) compared with placebo. Active treatment significantly reduced the risk of pneumonia among participants of Asian ethnicity (47%, 14-67%; p = 0.01), with no significant effect among non-Asian participants (5%, -27 to 29%; p = 0.7) (p for homogeneity = 0.04). These findings substantially add to the body of evidence about the effects of these drugs on pneumonia but do not provide the definitive information required to inform clinical decisions about the prevention of pneumonia with ACE inhibitors.